2022
DOI: 10.3389/fgene.2022.927614
|View full text |Cite
|
Sign up to set email alerts
|

Nine-gene signature and nomogram for predicting survival in patients with head and neck squamous cell carcinoma

Abstract: Background: Head and neck squamous cell carcinomas (HNSCCs) are derived from the mucosal linings of the upper aerodigestive tract, salivary glands, thyroid, oropharynx, larynx, and hypopharynx. The present study aimed to identify the novel genes and pathways underlying HNSCC. Despite the advances in HNSCC research, diagnosis, and treatment, its incidence continues to rise, and the mortality of advanced HNSCC is expected to increase by 50%. Therefore, there is an urgent need for effective biomarkers to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Furthermore, we compared the previous GPCR-based model with other models from previous studies. 23 , 24 , 25 , 26 As indicated by C-index comparison, the GPCR-based model outperformed them in predicting OS for HNSCC patients ( Figure S4 ). Moreover, we constructed a nomogram based on GPR87, S1PR4, and S1PR5 expressions ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, we compared the previous GPCR-based model with other models from previous studies. 23 , 24 , 25 , 26 As indicated by C-index comparison, the GPCR-based model outperformed them in predicting OS for HNSCC patients ( Figure S4 ). Moreover, we constructed a nomogram based on GPR87, S1PR4, and S1PR5 expressions ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 89%
“…Growth differentiation factor-10 (GDF10), also known as BMP3b, is a tumor suppressor that belongs to the transforming growth factor-b (TGF-b) superfamily ( Cheng et al, 2016 ). CIB1, PIM3, SLC16A3, VOPP1, BMP4, TIGIT, ADAR, and LRRN4CL are studied as upregulated genes in various cancer types such as squamous carcinoma cells, breast cancer, head and neck squamous cell carcinoma, and pancreatic cancer ( Baras et al, 2011 ; Alarmo et al, 2013 ; Zheng and Tian, 2014 ; de Jong et al, 2018 ; Notarangelo, 2018 ; Broutian et al, 2020 ; Yu et al, 2020 ; Huo et al, 2021 ; Wen et al, 2021 ; Yang et al, 2022 ). A complex that is important in the keratinocyte-intrinsic immune response to human papillomaviruses (-HPVs) is formed when CIB1 interacts with the EVER1, and EVER2 proteins ( de Jong et al, 2018 ; Notarangelo, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of GTSE1 in drug resistance is shown in gastric cancer cells [ 24 ], osteosarcoma [ 25 ], breast cancer [ 23 ], clear cell renal cell carcinoma [ 19 ], and non-small-cell lung cancer [ 26 ]. In addition, GTSE1 is demonstrated to be involved in apoptosis in clear cell renal cell carcinoma [ 20 ], gastric cancer cells [ 24 ] and esophageal squamous cell carcinoma [ 27 ], and it was also involved in Warburg effect in cervical cancer [ 28 ].Furthermore, GTSE1 has been identified to be upregulated in head and neck squamous cell carcinoma (HNSC) [ 13 ], and GTSE1 can act as one of nine genes contributing to build the model for the prognostic risk prediction of HNSC [ 29 ], which indicated that GTSE1 might be involved in the progression of NPC.…”
Section: Introductionmentioning
confidence: 99%